Self-massage and autonomic response: Future direction - Rios Monteiro, E.; Wakefield,B.; Gomes Ferreira de Melo Fiuza, A.; de Oliveira Muniz Cunha, J. C.; Goncalves Correa Neto, V.; da Silva Novaes, J. (Journal of Exercise, Sport & Orthopedics, 2017)
Self-massage (SM) is an active technique where participants use various instruments to apply pressure to soft tissue with an attempt to mimic manual therapy techniques. Within the literature, there are many techniques associating positive responses to the phenomena controlled by the central nervous system (i.e. stretching and manual therapies). The purpose of this short communication is to present the literature regarding similar techniques to SM and their effects on the central nervous system. Furthermore, there is no research investigating the safety of performing SM techniques prior to performance. Considering SM is non-invasive and practical, findings of such research would be applicable in clinical and performance settings. Thus, the authors encourage further research that satisfies the needs of these gaps.